High-resolution HPV genotyping uncovers genotype-specific trends - Abdul Halim, Sarah; A.Talib, Norlelawati; Mohamed, Nurdiyana (2025)
Introduction: Human papillomavirus (HPV) is a circular, double-stranded DNA virus with genotype-specific oncogenic potential. Given the differential oncogenicity of individual genotypes, precise molecular typing is essential for genomic surveillance, risk stratification, and evaluation of vaccine efficacy across populations. Material and Methods: A total of 3,814 cervical specimens were retrospectively analysed from patients attending Sultan Ahmad Shah Medical Centre, SASMEC@IIUM between 2018 and 2024. Genomic DNA was extracted and subjected to multiplex real-time PCR-based genotyping. Specimens collected from 2018 through February 2024 were tested using the Anyplex™ II HPV28 Detection assay, while those from March 2024 onward were processed with the Allplex™ HPV28 Detection kit (Seegene, Inc.). Both platforms utilise proprietary TOCE™ (Tagging Oligonucleotide Cleavage and Extension) and DPO™ (Dual Priming Oligonucleotide) technologies, enabling high-specificity, high-throughput simultaneous detection of 28 HPV genotypes in a single reaction. Results: HPV DNA was identified in 8.6% of cases. High-risk (HR) genotypes dominated the landscape, with HPV-52 (11.4%), HPV-66 (9.5%), and HPV-18 (8.0%) being the most prevalent. HPV-18 demonstrated consistent annual detection, whereas HPV-52 showed an incremental rise in prevalence from 0.8% in 2019 to 1.3% in 2024, indicating potential genotype replacement or selective pressure effects. Low-risk genotypes such as HPV-6 and HPV-11 were less commonly detected. Conclusion: This study illustrates the diagnostic value of multiplex molecular platforms in delineating genotype-specific HPV trends. The emerging increase in HPV-52 prevalence highlights the need for sustained molecular monitoring to guide regional vaccination strategies and refine diagnostic algorithms.